基于Zigbee网络的气体监控系统 (2018)
本发明涉及种基于Zigbee网络的气体监控系统，包括：实时监测涉气设备的Zigbee无线监测节点，Zigbee无线监测节点包括气敏传感器模块和Zigbee终端模块；Zigbee协调器，与Zigbee无线监测节点建立无线通信连接以汇总Zigbee无线监测节点上传的采集数据；与Zigbee协调器通信连接的控制主机，包括数据存储器、故障报警器、安全继电器和微处理器，微处理器在分析得到采集数据中气体浓度超过预设的气体浓度阈值时触发故障报警器予以报警并控制安全继电器将对应的涉气设备予以关断。相较于现有技术，本发明基于Zigbee网络的气体监控系统，充分利用Zigbee的自组织网络特点以及安全继电器的自诊断和冗余容错功能，利用两者的优点结合对车间设备进行安全可靠控制，提高车间工作环境的安全性。 The invention relates to a gas monitoring system based on a Zigbee network. The gas monitoring system comprises Zigbee wireless monitoring nodes used for monitoring gas-related devices in real time, a Zigbee coordinator and a control host. Each Zigbee wireless monitoring node comprises a gas sensor module and a Zigbee terminal module. The Zigbee coordinator is in wireless communication with the Zigbee wireless monitoring nodes so as to collect the collected data uploaded by the Zigbee wireless monitoring nodes. The control host is in communicated with the Zigbee coordinator and comprises a data memorizer, a fault alarm, a safety relay and a microprocessor. The microproc